P503 Two year experience with vedolizumab in inflammatory bowel disease patients: results of the ICC case series, a nationwide prospective observational cohort study. (25th January 2019) - Biemans, V; van der Woude, J; Dijkstra, G; van der Meulen-de Jong, A; Oldenburg, B; de Boer, N; Löwenberg, M; Srivastava, N; Jansen, J; West, R; de Vries, A; Haans, J; et al.
Abstract: Background: Vedolizumab (VDZ) is approved for the treatment of inflammatory bowel disease (IBD). Prospective data on clinical effect, safety and usage beyond 1 year of follow-up is scarce. We aimed to study the two year real-life experience with VDZ in IBD patients. Methods: IBD patients initiating VDZ treatment were prospectively enrolled in a nationwide, web-based registry: the ICC case series. Clinical activity scores (Harvey–Bradshaw Index (HBI) for Crohn's disease (CD), Short Clinical Colitis Activity Index (SCCAI) for ulcerative colitis (UC)), biochemical parameters (C-reactive protein (CRP) and faecal calprotectin (FCP)), VDZ dosage, concomitant medication, and adverse events were documented at week 0, 12, 24, 52, and 104, or when VDZ treatment was discontinued. Clinical remission was defined as HBI ≤4 and SCCAI ≤2. Biochemical remission was defined as a CRP concentration ≤5 mg/l and/or FCP level ≤200 µg/g. Intention-to-treat (ITT) follow-up was determined between first visit and last visit included in the ITT analysis. Results: In total, 275 IBD (173 CD, 102 UC) patients were included (98.9% and 89.2% anti-tumour necrosis factor (TNF) exposed, respectively), with a median follow-up period of 104.0 weeks (IQR 100.7–104.0) for CD and 104.0 weeks (IQR 56.8–104.0) for UC. The proportion of patients in steroid-free clinical remission at Week 52 and 104 was 28.0% and 27.5% for CD and 33.7% and 30.9% for UC, respectively. Between Week 52 and 104, 73.7% of the CD and 73.1% of the UC patients remained in steroid-free clinical remission. clinical effect was comparable for combination of VDZ and immunosuppressive agents vs. VDZ monotherapy (Week 104: 29.5% vs. 28.4% p = 0.86). The proportion of patients in biochemical remission at Week 52 and 104 was 26.5% and 21.0% for CD and 30.6% and 22.2% for UC, respectively. An additional infusion at Week 10 was given to 83 (48.0%) CD and 17 (16.7%) UC patients, 40 (23.1%) CD and 13 (12.7%) UC patients underwent interval shortening (≤6 weeks). Ten severe infections occurred resulting in hospital admission (3.4 per 100 patients years), 8/10 used concomitant immunosuppressive agents. VDZ was discontinued in 100 (57.8%) CD and 47 (46.1%) UC patients, mainly due to primary non-response (CD: 61%, UC: 85.1%). Nine patients discontinued VDZ due to adverse events (3.1 per 100 patient-years). Twenty-six (CD: 22, UC: 4) patients discontinued after the first year. Conclusions: We assessed clinical outcomes of VDZ in a nation-wide, prospective cohort of anti-TNF experienced IBD patients with 104 weeks follow-up. Our data showed persistent effectiveness of VDZ beyond 52 weeks of treatment, as well as frequent dosage optimisation and a reassuring long-term safety profile.